World War I and Propaganda - Paddock, Troy R. E. (Brill, 2014)
World War I and Propaganda offers a new look at a familiar subject. The contributions to this volume demonstrate that the traditional view of propaganda as top-down manipulation is no longer plausible. Drawing from a variety of sources, scholars examine the complex negotiations involved in propaganda within the British Empire, in occupied territories, in neutral nations, and how war should be conducted. Propaganda was tailored to meet local circumstances and integrated into a larger narrative in which the war was not always the most important issue. Issues centering on local politics, national identity, preservation of tradition, or hopes of a brighter future all played a role in different forms of propaganda. Contributors are Christopher Barthel, Donata Blobaum, Robert Blobaum, Mourad Djebabla, Christopher Fischer, Andrew T. Jarboe, Elli Lemonidou, David Monger, Javier Pounce,Catriona Pennell, Anne Samson, Richard Smith, Kenneth Andrew Steuer, María Inés Tato, and Lisa Todd.
Publication Title: World War I and Propaganda
Keywords: dept.his